2017
DOI: 10.1111/lre.12182
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of the biology of Nile perch, Lates niloticus, in the open waters of Lake Victoria, Kenya

Abstract: Samples (6404) of Nile perch were collected monthly from commercial catches between June 2014 and June 2015. The total length (cm), weight (g) and sex of fish were all determined in the field, with 3771 (59%) being male and 2059 (32%) being female fish, for an overall sex ratio of 1.83:1.00 (male: female). The average length and weight for all fish were 55.38 ± 0.14 cm TL and 2355.10 ± 22.30 g, respectively. The size of male fish ranged from 15.5 to 128.5 cm TL and weighed between 190 and 25 000 g, whereas tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…The variations in b between study sites may be attributable to differences in the environmental conditions. The b value can be used as an indicator of food intake and may differ according to biotic and abiotic factors, food availability and habitat type (Yongo et al, ). Length–weight relationships for fish have been used extensively to provide information on the condition of fish and their isometric or allometric growth (Yongo, Outa, Kito, & Matsushita, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variations in b between study sites may be attributable to differences in the environmental conditions. The b value can be used as an indicator of food intake and may differ according to biotic and abiotic factors, food availability and habitat type (Yongo et al, ). Length–weight relationships for fish have been used extensively to provide information on the condition of fish and their isometric or allometric growth (Yongo, Outa, Kito, & Matsushita, ).…”
Section: Discussionmentioning
confidence: 99%
“…The most important commercial fish species in Lake Victoria until the 1960s were Schilbe intermedius , Protopterus aethiopicus , Claria s gariepinus, Bagrus docmak, Momyrids, Labeo victorionus, and the tilapiine species Oreochromis esculentu s and O. variabilis (Ogutu‐Ohwayo, ). When Lates niloticus , O. niloticus, O. leucostictus, Tilapia zillii and T. rendalii were introduced, the lake ecological system changed because of predation and competition for food (Yongo, Outa, Kito, & Matsushita, ). In the early 1990s, B. docmak , C. gariepinus and S. intermedius were the top predators in Lake Victoria (Corbet, ).…”
Section: Introductionmentioning
confidence: 99%
“…() reported that fish below and above the slot size has continued being caught and processed, thereby confirming the slot size is hardly adhered to by both the fishers and the processors . Reductions in the sizes of L. niloticus are likely attributed to the illegal gears and methods used in the fishery (Yongo et al, ). Fishers in Lake Victoria have increasingly abandoned large‐meshed gillnets in favour of small hooks on long lines (Mkumbo & Marshall, ), which largely targets small size Nile perch.…”
Section: Discussionmentioning
confidence: 99%
“…The increased condition of female and decreased conditions for males with increasing size, however, could be attributable to gonadal development and spawning conditions. In fact, the condition of fish is affected by changes in food availability, environmental quality, season and reproduction status, among other factors (Yongo, Outa, Kito, & Matsushita, ). Previous studies on the fecundity of R. argentea are summarized in Table .…”
Section: Discussionmentioning
confidence: 99%